Learning Reading Skills Using The Iqra Book Approach In Jordan Primary Schools - Diaya Uddeen Deab Mahmoud Alzitawi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Reading skills are one of the basic language skills in any language, and this study aims to find out the effectiveness of the book (Iqra) in developing basic level reading skills of students in Jordanian schools from underprivileged schools in Jordan. This study employs a descriptive approach, whereby the researcher has observed samples of 100 students from primary level in two schools, Al-Thunaibah primary school for male students and Al-Thunaibah primary school for female students. It consist of 20 students in a control sample, and 80 students in an experimental sample. The study found that students who learn reading skills using Iqra books shows improvement in reading ability compared to students who use traditional reading skills books. Keywords: Reading Skills, Iqra Book, Under-Privilege School.